Experimental and analytical study of upgraded reinforced concrete beams - Liew, Sai Cheng. (2008)
An investigation was carried out on the behaviour of beams upgraded by the jacketing method. In this method, external tensile and shear reinforcement were fixed to host T-beams and a jacket of concrete was provided around the new reinforcement using prepacked aggregate and pressure grouting.